PENGARUH MODEL PEMBELAJARAN TIME TOKEN TERHADAP HASIL BELAJAR PPKN PADA SISWA KELAS V SDN BIRINGKALORO KABUPATEN GOWA - Amsis, Nurcholifha; Suardi; Aba, Akbar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Time Token learning model on the Civics (PPKn) learning outcomes of fifth-grade students at SDN Biringkaloro, Gowa Regency. The study employed a quantitative approach with a pre-experimental One Group Pretest–Posttest design. The sample consisted of 24 students selected using a saturated sampling technique. Data were collected through tests, observation, and documentation, and analyzed using descriptive and inferential statistics (normality test and paired sample t-test with SPSS). The results showed an increase in the average score from 72.00 (pretest) to 92.00 (posttest), and learning mastery improved from 46% to 100%. The implementation of the learning model was categorized as very high (91%). The hypothesis test yielded a significance value of 0.000 (< 0.05), indicating that the Time Token learning model has a significant and positive effect on students’ Civics learning outcomes and enhances their active participation.